Agaricus karakensis sp. nov. (Agaricaceae, Agaricales), a new species from Pakistan - Ullah, Tauseef; Ullah, Khetab; Kamal, Asif; Saba, Malka (Phytotaxa, 2024)
There are around 500 species of saprobic basidiomycetes in the genus Agaricus, of which 21 are reported from Pakistan. In this study, Agaricus karakensis sp. nov. is described as a new species from the tropical semi-arid District Karak, Khyber Pakhtunkhwa, Pakistan. The taxonomic identification was based on morphological features and ITS-region of rDNA. Both, field data and morpho-anatomical characterizations support that our specimens belong to a new species of Agaricus section Bivelares from family Agaricaceae, order Agaricales. In the phylogenetic tree, A. karakensis fall in section Bivelares forming a sister branch with A. bitorquis. In this paper, the nearest falling species were also compared with our novel finding in morphology.